융합기술의 동향분석을 위한 의미론적 특허분석 접근 방법 - 토픽모델링과 교차영향분석의 활용 - 정병기; Jeong Byeongki; 김정욱; Kim Jungwook; 윤장혁; Yoon Janghyeok (지식재산연구, 2016)
기술발전의 양상이 다양화 및 복합화됨에 따라, 개별 기술들 간의 경계가 점차 희미해진 융합기술이 나타나게 되었다. 융합기술을 분석함에 있어, 정적인 특허 분류코드를 활용하는 기존 연구방법들은 새로이 나타나는 기술들을 정의하고 이들 간의 파급관계를 분석하는 데 한계점을 지닌다. 따라서 본 연구는 대량의 특허에 대해 토픽모델링과 교차영향분석을 활용하여 융합기술을 분석하는 의미론적 분석 접근법을 제안한다. 제안된 방법은 토픽모델링을 특허 텍스트에 적용하여 분석 대상기술 내에 존재하는 잠재적인 세부 기술분야를 도출한 후, 교차영향분석을 활용하여 발굴된 세부기술들 간의 파급관계를 담고 있는 기술확산 매트릭스를 생성한다. 다음으로, 본 연구는 생성된 기술확산 매트릭스를 이용하여 융합기술 내에 존재하는 기술분야 간의 관계 시각화 및 정보엔트로피를 이용한 기술분야 간의 확산관계 분석을 실시한다. 본 논문에서는 융합 범위가 넓고 응용이 활발한 나노기술에 대한 사례연구를 통해 제안된 방법의 활용성을 파악한다. 본 연구는 기존의 특허 분류코드를 이용한 연구에서는 불가능했던 기술들의 정의와 이들 간의 파급 관계를 파악할 수 있도록 하며, 따라서 빠르게 변화하는 기술에 대한 효율적 모니터링을 가능하게 하는 전문가 지원도구로 활용될 수 있을 것이다. As technologies have been increasingly complex and dynamic, barriers among different technologies are becoming blurred. Although studies based on patent classification codes have been proposed to analyze trends of convergence technologies, their limitations are caused by the difficulty to deal with newly emerging or converging technological topics. As a remedy, this paper proposes a semantic approach to identify trends of convergence technologies, by applying topic modeling and cross-impact analyses to massive patents related to a convergence technology. The proposed approach applies topic modeling analysis to the textual data of the patents to determine semantic technology subjects within a technology for analysis, and then a cross-impact analysis to identify technological diffusion relationships among pairs of the technology subjects. Using the technology spreading matrix produced by the two techniques, this paper generates a network visual to show the interactive relationship among sub-technology subjects in the convergence technology and carries out technological diffusion analyses using the information entropy. This approach is illustrated using the patents related to nanotechnology, which is a representative technology with a variety of convergence applications. This approach allows experts to identify the appearance and relationship of new technologies or converged technologies that may not be recognized by patent classification codes, so it is expected that this approach would assist technology experts in monitoring sub-technologies and their technological spreading within a convergence technology field.